Spreadability and hate speech of radical conservatism: The Peruvian case on TikTok - Kanashiro Nakahodo, Lilian (2023)
This study aimed to establish a typology of the modes of spreadability of hate speech by radicalized conservative groups. Using Veron’s semiotic model, we focused on three analytical dimensions of circulation: temporalization, spatialization, and tracking. This approach helped us understand the qualities of spreadability inherent in hate speech. Employing a qualitative methodological strategy, we selected a corpus of 188 videos featuring Peruvian radical conservatives on TikTok. Through this analysis, we identified four modes of spreadability among conservative groups on TikTok: contagion, propagation, contamination, and population. The modes of spread-ability through contagion and propagation generate themes of change. Spreadability through contamination and population upholds the preservation of the past. The contribution of this study lies in explaining how the modes of circulation for conservative hate speech function as strategies within a cultural war aimed at ideological entrenchment. © 2023 Elder Cuevas Calderón, Eduardo Yalán Dongo and Lilián Kanashiro.